Urban Climate, Heat Islands and Thermal Comfort in the Neighborhoods of Cabula and Pernambués in the Urban Center of Salvador (BA) - Ferreira, Bárbara Carlos; Estevam, André Luiz Dantas; Maia, Diego Corrêa [UNESP] (Revista Brasileira de Geografia Fisica, 2022)
The objective of this research was to analyze the heat islands in the city of Salvador in the neighborhoods of Cabula and Pernambués both located in the urban core area of the city. The relevance of geographic factors of location, altitude, influence of sea and continental breeze systems, as well as the effect of heating of surface areas to urban land use were addressed. The theoretical and methodological conception of the Urban Climate System. In this context, maps of land uses of localities were generated through the arcview 9.1 programa. Subsequently, surface temperatures were made through infrared sensor thermometers through the various types of ground cover through technical visits to several streets and avenues in the neighborhoods. This information supported the organization of the final report of the research that used the Thermal Discomfort Index (ID). The use of ID has extreme relevance because it seeks to establish correlations between heat islands and physical discomfort that has a direct impact on people's health and quality of life. In the neighborhoods of Pernambués and Cabula, discomfort zone classes were identified. However, it is worth highlighting the relevance of the fragment of the Dense Ombrófila Forest as a fundamental element in the establishment of a frescor island in the Cabula neighborhood.
Clima Urbano, Ilhas de Calor e Conforto Térmico nos Bairros do Cabula e Pernambués no Centro Urbano de Salvador (BA)
Keywords: geographic factors; heat islands; land use; thermal discomfort; urban climate system